Targeting for Social Safety Nets : Evidence from Nine Programs in the Sahel - Schnitzer, Pascale; Stoeffler, Quentin (World Bank, Washington, DC, 2021)
Proxy-Means Testing (PMT) and Community-Based Targeting (CBT) are among the most widely used methods for poverty targeting in low-income settings. This paper analyzes household data from nine programs implemented in the Sahel region using a harmonized approach to compare PMT and CBT selection as conducted in practice, once geographical targeting has been applied. The results show that the targeting performance measured depends critically on the definition of the targeting objectives, share of beneficiaries selected, and indexes used to evaluate targeting. While PMT performs better in reaching the poorest households based on per capita consumption, it differs little from CBT, or a random or universal allocation of benefits when distances to poverty lines are considered. When aiming to identify food insecure households, most PMT and CBT targeting schemes perform no better than a random allocation of benefits. On the other hand, targeting costs represent only a small share of budgets. Overall, the results emphasize the need to study programs as implemented in practice instead of relying on simulations of targeting performance, as widely used by practitioners and academics. Taken together, the findings suggest that while there may be a need to select households resulting from budget constraints, PMT and CBT contribute little to poverty or food insecurity reduction efforts in poor and homogeneous settings.